ANALISIS PEMBERIAN INSENTIF PADA RUMAH SAKIT UMUM DAERAH KOTA BOGOR - Ibrahim, Iim; Maruapey, Muhamad Husein; Luthfie, Muhammad (Administratie: Jurnal Administrasi Publik, 2023)
This research is motivated by the issues faced by employees in receiving incentives that are not proportionate to their workload, the lack of balance between employee rights and obligations, including weak work ethics among employees. The purpose of this study is to analyze the provision of incentives at the Regional General Hospital of Bogor City. This research utilizes descriptive analysis method with a population of 800 employees, from which a sample of 89 respondents is obtained using the Yamane formula. Data is collected through questionnaires, interviews, observations, and documentation and literature studies. The collected data is then analyzed using the Likert scale and Weighted Mean Score. The research results show that the average value of all dimensions in the focus of incentive provision is 2.98 with a fairly good category. This is due to the existing mismatch between incentives and employee workloads, leading to implications for employee performance and service to the community accessing healthcare facilities.